Coffee, Caffeine, and Health Outcomes: An Umbrella Review - Grosso, Giuseppe; Godos, Justyna; Galvano, Fabio; Giovannucci, Edward L (Annual review of nutrition, 2017)
To evaluate the associations between coffee and caffeine consumption and various health outcomes, we performed an umbrella review of the evidence from meta-analyses of observational studies and randomized controlled trials (RCTs). Of the 59 unique outcomes examined in the selected 112 meta-analyses of observational studies, coffee was associated with a probable decreased risk of breast, colorectal, colon, endometrial, and prostate cancers; cardiovascular disease and mortality; Parkinson's disease; and type-2 diabetes. Of the 14 unique outcomes examined in the 20 selected meta-analyses of observational studies, caffeine was associated with a probable decreased risk of Parkinson's disease and type-2 diabetes and an increased risk of pregnancy loss. Of the 12 unique acute outcomes examined in the selected 9 meta-analyses of RCTs, coffee was associated with a rise in serum lipids, but this result was affected by significant heterogeneity, and caffeine was associated with a rise in blood pressure. Given the spectrum of conditions studied and the robustness of many of the results, these findings indicate that coffee can be part of a healthful diet.